Lake Vättern Fish: From the Water to the Consumers : ecosystem-based fisheries management assessment, fish & fish products distribution channels of lake Vättern - Isimemen-Wealth, Felix (SLU/Department of Molecular Sciences, 2021)
This study assessed the Ecosystem-Based Fisheries Management (EBFM) of Lake Vättern by using the EBFM objectives as spelt out by Engler et al. (2015) and Long et al. (2015). In order to fully understand the fish and fish products distribution channels, it was necessary to understand the lake’s fisheries and their management. This is because a perturbation at any stage of the lake’s fish supply chain could have resultant effects on other stages. On the other hand, this study traced the processing and distribution channels of commercial fish and fish products from Lake Vättern. Also, it examined the level of consumer-involvement (as stakeholders) in the ‘co-creation’ or co-management of the lake’s fisheries. The certification status of the lake’s fisheries, the impact of environmental toxins on fish products and consumers’ reactions were also studied. The assessment of the EBFM objectives shows that the lake’s fisheries co-management team is on the right path in sustainably managing the fisheries (fish production level), but ignores the processing, distribution and consumption stages of the lake’s fish supply chain. The co-management team engages relevant stakeholders in the lake’s management except the fish consumers who are not represented at all. The lake’s fisheries are not MSC-certified due to the issues of environmental toxins and invasive species. The lake’s signal crayfish, Arctic char and trout fisheries are the largest in terms of catch size and value. Fresh, filleted and smoked fish are the main fish and fish products commonly demanded for by consumers at the Lake Vättern region. These products are distributed through food restaurants, wholesalers, fish markets, fish shops and direct delivery by fishers to consumers. Many of the nineteen registered fishers of the lake process and retail their catches by themselves. The fish from the lake are not enough to meet local consumer demand, so fish are ‘imported’ to augment local supplies.